Determinação do coeficiente de digestibilidade aparente de alimentos para pintado amazônico (Pseudoplatystoma reticulatum x Leiarius marmoratus) - Marques, Soraia Andressa Dall` Agnol (2016)
The aim with this work to determine apparent digestibility coefficients (CD) of dry matter (DM), gross energy (EB) and crude protein (CP) of corn, dry beans solvent distillation (DDGS), blood meal and soy protein concentrate (SPC) for Amazon painted. 65 fish were used with 0.184 ± 0.70 kg average weight, divided into five groups. The fish were fed twice daily and stool samples, carried out through the indirect collection method with use of incubators circular conical-adapted, two were made in 2 hours. The feces collected were subjected to analyses qualitative characteristics. The determination of the CD was carried out through the analysis of chromium by atomic absorption espectofotômetro, through replacement of the test food for ration reference, using 0.1% chromium oxide as indicator. I concluded that the digestibility coefficients of PB, EB, and MS were respectively of 64.64; 58.16 and 65.99% bloodmeal, 53.41; 81.62 and 62.81 to CPS, 21.96; 66.06 and 28.52% of DDGS and 44.48; 70.03 and 47.77% for maize.